As aspirações do povo de Deus: um estudo de caso em duas CEBs de São Paulo (SP) (1980-2010) - Juliani, Jhonny (2012)
This study aimed to understand the goals of the lay members of two BECs - Basic Ecclesial Communities - between 1980 and 2010. For this purpose, initially, following the epistemological orientation of Max Weber, values that guide social action of these members were analyzed. Then, we tried to identify the objectives of lay people through the interpretation of the documents produced by interchurch meetings of BECs. Finally, we conducted a field survey in two communities: Maria Mãe dos Migrantes and São José Operário. The research has inferred that there were significant changes in the values and purposes of the social actions of lay members over the past three decades